Internal Combustion Engines and Powertrain Systems for future Transport 2019 (Taylor & Francis, 2020)
Internal Combustion Engines and Powertrain Systems for Future Transport 2019 provides a forum for IC engine, fuels and powertrain experts, and looks closely at developments in powertrain technology required to meet the demands of the low carbon economy and global competition in all sectors of the transportation, off-highway and stationary power industries.